Stuart Davis - in full swing - Haskell, Barbara 1946-; Cooper, Harry 1959- (DelMonico Books, Prestel, 2016)
"Hailed as a precursor of both pop art and contemporary abstraction, Stuart Davis captured the energy of mass culture and modern life. Beginning in 1921, a series of breakthroughs led him to develop a more abstract approach. Fusing American urban experience with European modernism, his style evolved over the next four decades to become a dominant force in postwar art. The book features some 100 works, from his 1921 paintings of tobacco packages to his abstract Egg Beater series of the late twenties, the ambitious WPA murals of the thirties, and the bold works of his last two decades, in which jagged shapes and bright colors tangle with vigorous calligraphy. The volume pays special attention to his transformative recycling of earlier works; and a chronology-drawing on previously unpublished sources-represents the most complete biography to date, painting a vivid picture of economic hardship, political activism, personal struggle, and eventual triumph"...
Includes bibliographical references and index. - Exhibition dates: Whitney Museum of American Art, New York, June 10-September 25, 2016 ; National Gallery of Art, Washington, November 20, 2016-March 5, 2017 ; de Young, Fine Arts Museums of San Francisco, April 8-August 6, 2017 ; Crystal Bridges Museum of American art, Bentonville, Arkansas, September 16, 2017-January 8, 2018
Keywords: Davis, Stuart -- 1892-1964 -- Exhibitions; Davis, Stuart -- 1892-1964; ART / Individual Artists / Monographs; Jazz in art -- Exhibitions; Ausstellungskatalog; Ausstellungskatalog -- Crystal Bridges Museum of American Art -- 16.09.2017-08.01.2018 -- Bentonville, Ark.; Ausstellungskatalog -- De Young Museum -- 08.04.2017-06.08.2017 -- San Francisco, Calif.; Ausstellungskatalog -- National Gallery of Art -- 20.11.2016-05.03.2017 -- Washington, DC; Ausstellungskatalog -- Whitney Museum of American Art -- 10.06.2016-25.09.2016 -- New York, NY